Vitamin d and leishmaniasis: Neither seasonal nor risk factor in canine host but potential adjuvant treatment through cbd103 expression. - Clara Martori (Public Library of Science (PLoS), 2021)
Vitamin D (VitD) deficiency has been shown to be a risk factor for a plethora of disorders. We have shown that dogs with clinical leishmaniasis presented lower VitD serum levels than non-infected dogs, and even lower than those with asymptomatic infection. However, if VitD deficiency is a risk factor to develop clinical leishmaniasis remains to be answered. It is also unknown if VitD participates in Leishmania control. First, we retrospectively analysed VitD concentration in serum samples from 36 healthy dogs collected in different periods of the year concluding that there isn't a seasonal variation of this vitamin in dogs. We also included 9 dogs with clinical leishmaniasis and 10 non-infected healthy dogs, in which we measured VitD levels at the beginning of the study, when all dogs were negative for serology and qPCR, and 1 year later. Whereas non-infected dogs showed no change in VitD levels along the study, those developing clinical leishmaniasis showed a significant VitD reduction at the end of the study (35%). When we compared VitD concentration between the two groups at the beginning of the study, no differences were detected (43.6 (38-59) ng/mL, P = 0.962). Furthermore, an in vitro model using a canine macrophage cell line proved that adding active VitD leads to a significant reduction in L. infantum load (31.4%). Analyzing expression of genes related to VitD pathway on primary canine monocytes, we showed that CBD103 expression was significantly enhanced after 1,25(OH)2D addition. Our results show that VitD concentration is neither seasonal nor a risk factor for developing canine leishmaniasis, but it diminishes with the onset of clinical disease suggesting a role in parasitic control. Our in vitro results corroborate this hypothesis and point out that VitD regulates infection through CBD103 expression. These results open the possibility for studies testing VitD as an adjuvant in leishmaniasis therapy.